2020
DOI: 10.1097/jom.0000000000001999
|View full text |Cite
|
Sign up to set email alerts
|

Personal Protective Equipment and Mental Health Symptoms Among Nurses During the COVID-19 Pandemic

Abstract: Objective: To determine the association between access to adequate personal protective equipment (PPE) and mental health outcomes among a sample of U.S. nurses. Methods: An online questionnaire was administered in May 2020 to Michigan nurses via three statewide nursing organizations (n = 695 respondents). Multivariable logistic regression analysis was used to identify factors associated with mental health symptoms. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
147
4
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(176 citation statements)
references
References 17 publications
14
147
4
11
Order By: Relevance
“…The final search resulted in a total of eight studies enrolled in the qualitative synthesis. The eight studies were of cross-sectional design and are summarized by characteristics in Table 1, quality in Table 2, and estimates (prevalence and odds ratio) in Table 3 [3,[20][21][22][23][24][25][26]. Six of the eight studies reported PTSD symptoms among healthcare professionals during the COVID-19 pandemic in Asia (China [20][21][22], Singapore [3], and India [3]) and North America (United States of America [23,24]), while two studies were undertaken during the SARS-2003 pandemic in Asia (China [25] and Singapore [26]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final search resulted in a total of eight studies enrolled in the qualitative synthesis. The eight studies were of cross-sectional design and are summarized by characteristics in Table 1, quality in Table 2, and estimates (prevalence and odds ratio) in Table 3 [3,[20][21][22][23][24][25][26]. Six of the eight studies reported PTSD symptoms among healthcare professionals during the COVID-19 pandemic in Asia (China [20][21][22], Singapore [3], and India [3]) and North America (United States of America [23,24]), while two studies were undertaken during the SARS-2003 pandemic in Asia (China [25] and Singapore [26]).…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies self-reported level of exposure to coronaviruses (CoV-1 or CoV-2) and severity of PTSD symptoms using paper or online surveys with a response rate above 80% [3,25], of 60-80% [20][21][22]26], and below 15% [23,24]. Three studies were conducted in a single hospital [21,25,26], three studies were conducted in multiple hospitals [3,20,22], one study was conducted in a single state [23], and two studies were conducted in multiple states or provinces [20,24]. Two studies were investigated merely nursing staff [22,23], one study had a majority of female nursing staff (93.6%) [23], one study recruited just otolaryngology physicians [24], and two studies focused on nurses and doctors [20,26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies on COVID-19 were published in China (n = 32) [67, 73-76, 84-86, 88, 91-93, 95-97, 99, 101, 102, 107, 110, 113, 114, 116-119, 121-126] and Italy (n = 6) [71,72,78,79,83,103]. Other studies were conducted in the United States [68,89,106], Iran [100,105,112], Turkey [80,104,111], Germany [90,120], Pakistan [66,87], Poland [115], India [108], Egypt [81], Brazil [77], France [70], Spain [94], Saudi Arabia [98], and Singapore [109]. Two studies recruited participants from different countries [69,82].…”
Section: Characteristics Of Primary Studiesmentioning
confidence: 99%
“…However, more information is needed about how these relationships might unfold in working populations, both to contribute to theory building and to inform potential interventions. Useful starting points to this research would include extending previous research on mental health concerns such as depression, anxiety, and post‐traumatic stress disorder (Arnetz, Goetz, Sudan, Arble, Janisse, & Arnetz, 2020; Sampaio, da Cruz Sequeira, & da Costa Teixeira, 2020; Wilson, Lee, Fitzgerald, Oosterhoff, Sevi, & Shook, 2020), occupation‐specific outcomes such as burnout, and positive psychology outcomes such as subjective well‐being or the experience of work as meaningful. Longitudinal research would be especially valuable (see Zacher & Rudolph, 2020 for an example).…”
Section: Introductionmentioning
confidence: 99%